2015
DOI: 10.1016/j.aquatox.2014.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Parental exposure to environmental concentrations of diuron leads to aneuploidy in embryos of the Pacific oyster, as evidenced by fluorescent in situ hybridization

Abstract: Changes in normal chromosome numbers (i.e. aneuploidy) due to abnormal chromosome segregation may arise either spontaneously or as a result of chemical/radiation exposure, particularly during cell division. Coastal ecosystems are continuously subjected to various contaminants originating from urban, industrial and agricultural activities. Genotoxicity is common to several families of major environmental pollutants, including pesticides, which therefore represent a potential important environmental hazard for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 56 publications
0
14
0
Order By: Relevance
“…Genotoxicity on gamete and somatic cells (Bouilly et al 2007;Akcha et al 2012;Barranger et al 2014), embryotoxicity (Akcha et al 2012;Barranger et al 2014) and immunotoxicity (Gagnaire et al 2007;Luna-Acosta et al 2012;Barranger et al 2015) were already reported after exposure to 0.05 to 3.00 μg.L -1 of diuron depending on the studies. As already demonstrated for other herbicides such as paraquat, glyphosate and atrazine, ROS production could also be involved in the toxicity of diuron (Glusczak et al 2006;Awadalla 2012;Blahová et al 2013;Griboff et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Genotoxicity on gamete and somatic cells (Bouilly et al 2007;Akcha et al 2012;Barranger et al 2014), embryotoxicity (Akcha et al 2012;Barranger et al 2014) and immunotoxicity (Gagnaire et al 2007;Luna-Acosta et al 2012;Barranger et al 2015) were already reported after exposure to 0.05 to 3.00 μg.L -1 of diuron depending on the studies. As already demonstrated for other herbicides such as paraquat, glyphosate and atrazine, ROS production could also be involved in the toxicity of diuron (Glusczak et al 2006;Awadalla 2012;Blahová et al 2013;Griboff et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Some results were previously obtained demonstrating both direct and indirect effects of the parental herbicide exposure on oyster genome. A genotoxic effect has been detected through the evidence of primary DNA damages in both somatic, germinal and reproductive cells of diuron-exposed genitors [ 37 , 38 ]. Moreover, the vertical transmission of damaged DNA was confirmed by the detection of chromosomal abnormalities in the offspring (DNA aneuploidy) [ 38 ].…”
Section: Introductionmentioning
confidence: 99%
“…A genotoxic effect has been detected through the evidence of primary DNA damages in both somatic, germinal and reproductive cells of diuron-exposed genitors [ 37 , 38 ]. Moreover, the vertical transmission of damaged DNA was confirmed by the detection of chromosomal abnormalities in the offspring (DNA aneuploidy) [ 38 ]. By a transcriptional approach, we showed that exposure of oyster genitors to diuron at environmental concentrations affected gene expression including genes encoding enzymes involved in DNA methylation machinery [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Agrochemical inputs are known to display seasonal variations: in France, high pesticide concentrations have been detected in spring in a major shellfish farming zone, the Marennes Oleron basin, corresponding to the highly-sensitive oyster gametogenesis period (Burgeot et al, 2008;Munaron, 2004;Soletchnik et al, 2005). Pesticides not only have direct toxic effects on adult oysters, but also indirect trans-generational effects on their offspring (Barranger et al, 2015(Barranger et al, , 2014Bouilly et al, 2007Bouilly et al, , 2003. In a previous experiment conducted by our laboratory, oyster genitors in gametogenesis were subjected to short exposures (two 7-day pulses) of environmental concentrations of the herbicide diuron (0.3 µg.L −1 ).…”
Section: Introductionmentioning
confidence: 99%